Application of manure and NPK fertilizer on Grobogan variety and Aochi/W-C-6-62 soybean as promise line in lowland Vertisol Ngawi, Indonesia - HENNY KUNTYASTUTI; SRI AYU DWI LESTARI (Nusantara Bioscience, 2017)
Kuntyastuti H, Lestari SAD. 2017. Application of manure and NPK fertilizer on Grobogan variety and Aochi/W-C-6-62 soybean as promise line in lowland Vertisol Ngawi, Indonesia. Nusantara Bioscience 9: 120-125. The effort to increase the productivity and production of soybean in lowland can be done with application of organic and/or inorganic fertilizer combined with promise line or large seed size soybean varieties that have high yield potential. Application of manure can increase soybean seed yield, but it needs a very high dose of more than 10 t manure/ha, so that often inhibits the supply, transportation, and application. The objective of this research was to evaluate the application of manure and NPK fertilizer on large seed size soybean which is Grobogan variety and Aochi/W-C-6-62 soybean as promise line in lowland Vertisol. The research was conducted in lowland Vertisol Ngawi on dry season (DS) 2011. The experiment used factorial randomized complete block design with three replications. The first factor was four doses of manure and the second factor was four doses combination of NPK fertilizer. The result showed that, on Vertisol soil Ngawi, Grobogan variety soybean need 2.5 t manure/ha to increase yield from 1.65 t/ha to 1.84 t/ha. To get a high yield of Aochi/W-C-6-62 soybean as promise line, there is two options fertilization. Aochi/W-C-6-62 need 7.5 t manure/ha to increase yield from 1.76 t/ha to 2.05 t/ha without inorganic fertilizer. Aochi/W-C-6-62 need 50 kg ZA + 150 kg SP-36 + 50 kg KCl/ha, but does not require additional manure to achieve 2.05 t/ha.